Clinical Efficacy of Follitropin Alfa in GnRH-Antagonist Protocols: A Prospective Observational Phase IV Study on the Use of Biosimilar Follitropin Alfa r-hFSH in Assisted Reproductive Technology in a Routine Care Setting - G Griesinger; T Schill; M Sator; M Schenk; JS Krüssel (JRI, 2021)
Background: This phase IV routine care study evaluated ovarian responses when using a biosimilar follitropin alfa r-hFSH (Bemfola®) for controlled ovarian stimulation (COS) in women undergoing assisted reproductive technology (ART) treatment who were pituitary-suppressed with a gonadotrophin-releasing hormone (GnRH) antagonist. Methods: This multicenter, prospective, non-comparative, non-interventional study (Germany/Austria) was conducted with 885 women (Mean age of 34.0±4.4 years) for whom COS with Bemfola® and GnRH-antagonist for pituitary suppression were applied  as part of in vitro fertilization (IVF) treatment with/without intracytoplasmic sperm injection (ICSI) observing routine clinical-practice protocols. Primary endpoint was the number of retrieved cumulus-oocyte-complexes (COCs). Results: Among 986 ART cycles, COS was given for 9.9±1.8 days (First-day r-hFSH dose of 220.7±68.9 IU; mean total dose of 2184.3±837.5 IU). It was revealed that 99.1% of cycles resulted in follicular puncture, with mean of 10.7±6.6 oocytes retrieved. Successful fertilization took place after IVF/ICSI in 93.8% of follicular punctures. Freeze-all was performed in 14.2% of cycles. Fresh embryo transfer was performed in 76.9% of cycles with follicular puncture; mean day of transfer was 3.5±1.3 and average number of transferred embryos was 1.76±0.50. Clinical pregnancy rate was 30.2% of embryo-transfer cycles and 23.4% of started cycles. Sixty-nine reports of ovarian hyperstimulation syndrome (7.0% of started cycles) were documented. Conclusion: COS with Bemfola® in GnRH-antagonist IVF/ICSI protocols in a routine care setting led to an appropriate ovarian response allowing oocyte retrieval in 99.1% of initiated cases.